Advancements in Supercapacitor electrodes and perspectives for future energy storage technologies - Dar M.A.; Majid S.R.; Satgunam M.; Siva C.; Ansari S.; Arusalan P.; Rafi Ahamed S. (Elsevier Ltd, 2025)
Supercapacitors are promising energy storage devices for the future-generation world. They store energy through a charge separation mechanism and have high charge-discharge rates, specific energy and specific power. It compares supercapacitors with batteries regarding cycle life, efficiency, self-discharge, temperature sensitivity, maintenance, cost, and other applications. The previous review work primarily focused on advancements in electrode materials. The review highlights recent advancements in electrode nanotechnology, focusing on tailored nanostructures, advanced carbon nanomaterials, 2D nanomaterials, binder-free electrodes, nanocomposites and advanced characterization techniques. The challenges and limitations associated with supercapacitor electrodes and potential devices for improved performance are also discussed. Furthermore, the review explores the application of supercapacitors in electric vehicles, renewable energy integration, grid stabilization, and uninterruptible power supply systems. It also presents future perspectives on enhancing supercapacitor electrodes for sustainable and efficient energy storage. ? 2024 Hydrogen Energy Publications LLC